Excessive daytime sleepiness is associated with an increased frequency of falls and sarcopenia - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Background: This cross-sectional study aimed to examine associations between excessive daytime sleepiness (EDS) with falls and falls related conditions in older adults. Methods: To assess EDS, the Epworth Sleepiness Scale was used, with a score of >11/24 points indicating EDS. Number of falls and fall history (at least one) in the last year were recorded. Timed Up and Go test (TUG) was used to assess fall risk. Sarcopenia was defined by SARC-F tool. A grip strength score of the dominant hand, measured with a hand-grip dynamometer, less than 16 kg in females and 27 kg in males was accepted as dynapenia. Frailty status was defined by five dimensions including shrinking, exhaustion, low levels of activity, weakness, and slowness with those scoring positive on >3 dimensions being categorized as frail. The relationship between EDS with outcomes including fall, number of falls, falls risk, dynapenia, sarcopenia and frailty was investigated. Results: Of the 575 outpatients (mean age 78.7 +/- 7.5 years, female:70.4%), the prevalence of EDS was 19.8%. In the multivariable model adjusted for age, sex, living status, marital status, polypharmacy, osteoarthritis, Parkinson disease, depression and dementia; EDS was significantly associated with the number of falls last year (IRR = 1.94, 95% CI: 1.42-2.65) and sarcopenia (OR = 2.41, 95% CI: 1.41-4.12). EDS was not significantly associated with TUG based fall risk, frailty and dynapenia. Conclusions: EDS was observed in approximately one in every five older adults. EDS should be evaluated as part of geriatric assessment. Moreover, older patients with EDS should be further assessed for falls and sarcopenia.
Keywords: Excessive daytime sleepiness; Falls; Sarcopenia; Dynapenia; Frailty; OLDER-ADULTS; FRAILTY; RISK; DISTURBANCES; RELIABILITY; PERFORMANCE; DEPRESSION; DURATION; INJURIES; VALIDITY